In vitro activity of pyronaridine against multidrug-resistant Plasmodium falciparum and Plasmodium vivax. - Price, R; Marfurt, J; Chalfein, F; Kenangalem, E; Piera, K; Tjitra, E; Anstey, N; Russell, B (2010)
Pyronaridine, a Mannich base antimalarial, has demonstrated high in vivo and in vitro efficacy against chloroquine-resistant Plasmodium falciparum. Although this drug has the potential to become a prominent artemisinin combination therapy, little is known about its efficacy against drug-resistant Plasmodium vivax. The in vitro antimalarial susceptibility of pyronaridine was assessed in multidrug-resistant P. vivax (n = 99) and P. falciparum (n = 90) isolates from Papua, Indonesia, using a schizont maturation assay. The median 50% inhibitory concentration (IC(50)) of pyronaridine was 1.92 nM (range, 0.24 to 13.8 nM) against P. falciparum and 2.58 nM (range, 0.13 to 43.6 nM) against P. vivax, with in vitro susceptibility correlating significantly with chloroquine, amodiaquine, and piperaquine (r(s) [Spearman's rank correlation coefficient] = 0.45 to 0.62; P < 0.001). P. falciparum parasites initially at trophozoite stage had higher IC(50)s of pyronaridine than those exposed at the ring stage (8.9 nM [range, 0.6 to 8.9 nM] versus 1.6 nM [range, 0.6 to 8.9 nM], respectively; P = 0.015), although this did not reach significance for P. vivax (4.7 nM [range, 1.4 to 18.7 nM] versus 2.5 nM [range, 1.4 to 15.6 nM], respectively; P = 0.085). The excellent in vitro efficacy of pyronaridine against both chloroquine-resistant P. vivax and P. falciparum highlights the suitability of the drug as a novel partner for artemisinin-based combination therapy in regions where the two species are coendemic.